Cognitive Biases in Free- to-play Games - Behailu Shiferaw Benti; Dominika Hasse; Georg Stadtmann (Marketing Review St.Gallen, 2022)
Considering free-to-play games and their virtual currency exchange rate policies, we analyze the incidence of the cognitive biases "money illusion" and "decoy effect." We show that above par exchange rates and advertising bonus packs instead of price discounts in the in-game stores lead to adverse implications for the players. From our findings we derive managerial and policy implications.
Keywords: 650